A SYNOPTIC VIEW OF MUSIC SALES MANAGEMENT - BĂLAN, Oana Mihaela (Studia Universitatis Babes-Bolyai Musica, 2017)
The notion of marketing has a solid history and potential applicability in many fields. Literature has provided over time many definitions, directing the idea of marketing both to the scientific field, especially toward economic trends, and toward the social area, trying to influence the attitudes related to product marketing. If the domain in which we apply the marketing system is a musical one, its functions cannot be understood before clarifying the conditions under which the market is organized or the trade in goods is conducted, just as we cannot define some basic concepts without knowing the demands and needs of the people, or how to communicate and negotiate to satisfy their desires.